2020
DOI: 10.3389/fpsyg.2020.00790
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of Continuous Auditory and Visual Distractor Stimuli Is Leading to an Increased Performance

Abstract: Information across different senses can affect our behavior in both positive and negative ways. Stimuli aligned with a target stimulus can lead to improved behavioral performances, while competing, transient stimuli often negatively affect our task performance. But what about subtle changes in task-irrelevant multisensory stimuli? Within this experiment we tested the effect of the alignment of subtle auditory and visual distractor stimuli on the performance of detection and discrimination tasks respectively. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The application of such strict measures has caused an unprecedented disruption of the global societal and economic activities ( Asante and Mills, 2020 ), and affected the mental health of the general population ( Ozamiz-Etxebarria et al, 2020 , Rossi et al, 2020 ). Therefore, this necessitates the search for a more effective measure to control or possibly end COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The application of such strict measures has caused an unprecedented disruption of the global societal and economic activities ( Asante and Mills, 2020 ), and affected the mental health of the general population ( Ozamiz-Etxebarria et al, 2020 , Rossi et al, 2020 ). Therefore, this necessitates the search for a more effective measure to control or possibly end COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Although dependent on stimulus eccentricity, fusion of multisensory inputs has been proposed independent of task relevance. Previous studies have reported that even task‐irrelevant cross‐modal signals can exert a stronger interference on the currently performed task compared with a unimodal distractor (Heeman et al., 2016; Krause et al., 2012; Matusz et al., 2015, but an improvement in Mühlberg & Müller, 2020 and no effect in Experiment 4 of Lunn et al., 2019). Despite that no interference on the RSVP task was found in the present study, the pupillary light reflex induced by the visual stimuli that were task‐irrelevant and out of attentional focus was inhibited by temporally congruent tone pulses in Experiment 4.…”
Section: Discussionmentioning
confidence: 93%
“…So far, the visual flicker was always required to be attended as it was task‐relevant. Given several studies have found that even task‐irrelevant bimodal signals showed some signs of fusion relative to unimodal signals (Heeman et al., 2016; Krause et al., 2012; Matusz et al., 2015; Mühlberg & Müller, 2020), it is hypothesized that the inhibition of pupillary light reflex would not be affected despite the visual and auditory stimuli are task‐irrelevant and out of attentional focus. We conducted Experiment 4 to test this hypothesis.…”
Section: Methodsmentioning
confidence: 99%
“…This can be interpreted as a clear difference to the bottom-up and top-down 2D mechanism interaction with the 3D and AR modalities, which would be expected in cross-modal tasks (e.g., Parmentier et al, 2010;Mayas et al, 2014;Vasilev et al, 2019;Mühlberg and Müller, 2020).…”
Section: D and Ar On Gender And Videogame Applicationsmentioning
confidence: 87%